Algae salinity tolerance enhancement mediated by interaction with bacteria - Ng, Cheng Yee (2017)
This study investigates the mutualistic relationship between Chlamydomonas reinhardtii and Comamonas testosteroni I2 when cultured in 0.7% salinity TP media. When subjected to abiotic stresses, algal-bacterial co-culture yielded better growth compared to algal monoculture, a result which was observed across three bacterial strains. Specimens in saline media displayed higher chlorophyll concentrations in co-culture than in monoculture, and when cultivated in an environment of high surface area to volume ratio than in liquid suspension. Analysis of supernatant samples extracted and filtered from 96-well microplate samples indicated the production of organic carbon by alga, implicating cross-feeding between algae and vitamin B12-producing I2. Cell imaging provided visual evidence of bacterial biofilm formation surrounding algae cells.